Effect of progressive muscle relaxation technique on self-esteem and self-efficacy in multiple sclerosis patients: A clinical trial study - Ali Akbari; Farshid Shamsaei; Efat Sadeghian; Mehrdokht Mazdeh; Leili Tapak (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Low self-esteem and inefficiency are major problems in multiple sclerosis (MS) patients. A progressive muscle relaxation technique is one of the complementary therapies. The objective of this study was to investigate the effect of progressive muscle relaxation techniques on self-esteem and self-efficacy in MS patients. MATERIALS AND METHODS: This clinical trial was conducted on 100 MS patients were randomly divided into two groups of experimental (n = 50) and control (n = 50). The experimental group received progressive muscle relaxation techniques in eight 60-min sessions twice a week for 4 weeks. Rosenberg's Self-Esteem Scale and Self-Efficacy Scales of MS patients were completed before, immediately, and 4 weeks after the intervention. Data were analyzed using the SPSS software version 16. RESULTS: The mean score of self-esteem was not significantly different between the control (26.02 ± 5.83) and experimental (26.40 ± 6.06) groups before intervention (P = 0.247). The mean score of self-esteem in the control group (27.16 ± 7.45) and the experimental group (29.06 ± 6.61) immediately after the intervention (P = 0.083) was not significantly different. 4 weeks after the intervention, the mean scores of self-esteem in the control (26.96 ± 8.33) and the experimental (29.98 ± 7.02) groups were significantly different (P = 0.012). The mean score of self-efficacy was significantly different between the control (41.62 ± 4.46) and experimental (39.32 ± 4.31) groups before intervention (P = 0.010). The mean scores of self-efficacy in the control group (38.38 ± 5.07) and the experimental group (44 ± 4.46) immediately after the intervention (P < 0.001) and 4 weeks after intervention showed a significant difference between the control group (38.04 ± 5.46) and the experimental (46.40 ± 5.04) groups (P < 0.001). CONCLUSION: Due to the effect of progressive muscle relaxation on self-esteem and self-efficacy of MS patients, its safety and simplicity, this technique can be used as a complementary therapy to enhance the level of self-esteem and self-efficacy of MS patients.